2005
DOI: 10.1037/0022-0663.97.4.523
|View full text |Cite
|
Sign up to set email alerts
|

Is Educational Intervention Research on the Decline?

Abstract: The majority of studies included adults (age 18 and older) as participants, administered brief (less than 1 day) interventions, assessed intervention effects immediately following the intervention, and did not report treatment integrity. Most studies included multiple outcome measures and exhibited an increase in effect-size reporting from 4% in 1995 to 61% in 2004. The percentage of total articles based on randomized experiments decreased over the 21-year period in both the educational psychology journals (fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
1
8

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 30 publications
(55 reference statements)
4
72
1
8
Order By: Relevance
“…A review of educational psychology research found that less than 5 % of studies published in peer-reviewed journals accounted for time spent learning and time between learning and outcome measurement as factors (Hsieh et al 2005), indicating that the majority of educational psychology research is performed in abbreviated periods of time, usually less than 1 day. As discussed by Pouw, van Gog and Paas, embodied theories propose cognition consists of mental simulations that are grounded in sensorimotor experience.…”
Section: Future Directionsmentioning
confidence: 99%
“…A review of educational psychology research found that less than 5 % of studies published in peer-reviewed journals accounted for time spent learning and time between learning and outcome measurement as factors (Hsieh et al 2005), indicating that the majority of educational psychology research is performed in abbreviated periods of time, usually less than 1 day. As discussed by Pouw, van Gog and Paas, embodied theories propose cognition consists of mental simulations that are grounded in sensorimotor experience.…”
Section: Future Directionsmentioning
confidence: 99%
“…Thus, collaboration even with one's doctoral students would reduce perceptions of productivity in those cases. This was one of the reasons that Hsieh et al (2005) conducted their re-examination of scholarly productivity data previously reported by Smith and colleagues.…”
Section: Collaborationmentioning
confidence: 95%
“…Specifically, as Hsieh et al (2005) argued, higher ratings for productivity in previous studies (e.g., Smith et al 1998Smith et al , 2003 were awarded when the faculty solo-authored, had few co-authors and had high author placement in those publications than when they shared authorship. Thus, collaboration even with one's doctoral students would reduce perceptions of productivity in those cases.…”
Section: Collaborationmentioning
confidence: 97%
“…In one journal survey (Hsieh et al, 2005), the proportion of articles based on intervention and experimental (random assignment) methodology had decreased from 47% in 1983 to 23% in 2004.…”
Section: Correlational Data and Causal Conclusionmentioning
confidence: 99%